PENGARUH KEMAMPUAN BERPIKIR LOGIS MATEMATIS PADA ANAK USIA DINI DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN LOTTO DI KELOMPOK B - Hanifah, Masfufah; Alam, Syah Khalif (IKIP Siliwangi, 2019)
This study aims to determine how much influence the ability of logical-mathematical thinking in early childhood. Because children's mathematical abilities have not yet developed optimally, during the learning process it can be seen that the teacher's role is to emphasize more teacher-centered teaching. Cognitive development is one of the branches to develop children's thinking abilities especially in mathematical logical thinking. Color, and shape lotto are learning media that have a function to develop children's concentration and observation power. Therefore, the researchers used a quasi-experimental study that aims to see the effect on learning in the classroom by providing certain treatments in the experimental class while the control class is not given treatment. With the Wilcoxon trial to find out the effect on learning. ?Test Statistic? is known to ASMP value. SIG (2-tailed) is 0.001 smaller than <0. 05, it can be concluded that ?Hypothesis is accepted?, meaning there are differences between students' learning outcomes to improve the ability of logical-mathematical thinking for pretest and post-test. So, it can be concluded thus ?there is an influence in increasing the ability of logical-mathematical thinking in early childhood with lotto learning media in Group B.